Effect of a micronization method on the particle-size distribution and eluted phosphate-ion concentration for methane fermentation residue sludge. Issue 1 (31st December 2022) - Mori, Takamasa; Komiya, Yui; Yabe, Mitsuyasu
Abstract: Micronized methane fermentation residue sludge can be used as a liquid fertilizer because the micronized solid particles can be directly sprayed. Thus, the objective of this study was to clarify the effect of the micronization method on the particle-size distribution and eluted phosphate-ion concentration of sludge micronized by ultrasonication or ball milling. Although the average particle size in the sludge micronized by ball milling was 15 µm smaller than that micronized by ultrasonication, many finer particles (<10 µm) were observed in the ultrasonication-micronized sludge. Compared with untreated sludge, the concentration of the eluted phosphate ions of ultrasonication-micronized sludge was almost 15% higher, whereas that of the ball-milled sludge changed insignificantly. These results indicate that the particle sizes in the ball-milled and ultrasonication-micronized sludge were different, resulting in different phosphate ion elution behavior. Thus, the particle size and phosphate ion concentration can be controlled by changing and/or combining micronization techniques and optimizing their operating conditions.